Influence of workpiece preheating on chatter and machinability of Titanium alloy - Ti6Al4V - Amin, A. K. M. Nurul; Kamaruddin, K.; Abdelgadir, M. (IIUM Press, 2011)
Though classified as a group of “difficult-to-cut” material, titanium and its alloys are have wide applications in the aerospace industry owing to their unique high strength-weight ratio which is maintained at elevated temperatures and their exceptional corrosion resistance. In this work, experimental investigations of the influence of preheating using induction heating on machinability of titanium alloy Ti-6Al-4V ASTM B348 were conducted. Uncoated straight grade of cemented carbide inserts were used. The cutting speed was varied in the range from 40 to 160 m/min; with varying depths of cut and feed rates. The experiments of end milling operation conducted on Vertical Machining Centre (VMC) were design to look into vibration and chatter, chip formation, tool wear and surface finish. It has been established that the machinability of the investigated titanium alloy can be enhanced in terms of lower tool wear, better surface finish, lowering of instability of chip formation and chatter, increase in chip-tool contact length, shifting of the hot spot away from the tool edge and finally lowering of the dynamic stresses acting on the tool. Unique combinations of properties such as, high specific strength, which is maintained at elevated temperature, high fracture and corrosion resistance, have made titanium and its alloys very useful materials for aerospace and petrochemical applications. However their high cost and poor machinability are major constraints towards their wide spread applications. Ezugwu et al. [1] observed that success machining of titanium and its alloys depends largely on overcoming the problems associated with high cutting temperature and cutting pressures, small chip-tool contact length (which is about 1/3 that in the case of steel), serrated chip formation and chatter. Chatter is also undesirable because of its adverse effects on surface finish, machining accuracy and tool life [2]. Talantov and Amin [3] and Amin [4] established that chatter arises during machining when the frequency of the chip tooth serration coincides with any one of the natural frequencies of the system, such as the spindle, work, tool, fixtures, etc. According to Nakayama [5] and Konig et al [6] the chip formation mechanism is based on exceeding the critical shear stress under compressive and shear stresses. In order to get better machining, many methods of chatter control have so far been tried [7, 8]. The present work aims at investigating the influence of induction heating of the workpiece on improved machinability of the titanium alloy.